Simple Suturing Procedure to Manage a Flat Anterior Chamber Secondary to a Malfunctioned Ahmed Glaucoma Valve - Siamak Zarei-Ghanavati; Saeed Shokoohi-Rad; Mohammad Hashem Naseri; Reza Alizadeh (Patient Safety and Quality Improvement Journal, 2015)
Introduction: Presenting a case with repeated episodes of flat Anterior Chamber (AC) after Ahmed valve implantation, and suggesting a simple suturing procedure to manage these recurrences. Case:A 65-year-old woman presented to our clinic with uncontrolled Neovascular Glaucoma (NVG) in her left eye due to advanced Proliferative Diabetic Retinopathy (PDR) despite full medication to reduce Intraocular Pressure (IOP). After Ahmed valve implantation, anterior chamber became flattened spontaneously on postoperative day one. Therefore, we filled the AC with air at the first attempt but this procedure failed a day later. Then, we filled the AC with an ocular viscoelastic device. Because of these procedures failed to keep the AC formed, we hypothesized that it may be a malfunctioned valve. Therefore, we inserted 5-0 Nylon in Ahmed tube through AC and fixed it to the subconjunctiva two days after the second procedure. Anterior chamber remained deep and its shallowing did not occur despite removing the suture two weeks after the insertion. The IOP was controlled well with a functional filtering device at the last follow–up visit four months after the surgery. Conclusion: Spontaneous episodes of flat AC after Ahmed valve implantation in an eye can be well managed by inserting a removable suture into the Ahmed valve tube.